Basic Grammar: Understanding Vowels and Consonants in English - Barus, Putri Anantasari; Zhani, Vira Ulfia; Siregar, Fauzia Amelia Br.; Harahap, Ade Khofipah Indah; Lubis, Yani (Yayasan Daarul Huda Kruengmane, 2024)
An understanding of vowels and consonants is essential in learning English. In English, vowels and consonants play a role in forming words, facilitating effective communication, and forming distinctive phonemic patterns. This abstract highlights the importance of understanding these basic concepts. The focus includes vowel recognition, variations in pronunciation, and the role of each in the formation of words. A firm grasp of these concepts is important for improving English speaking and comprehension skills. Through a deep understanding, English learners can expand their vocabulary, improve conversation, and adjust to various communicative situations in English. This abstract highlights the urgency of this understanding in the context of English language learning and underlines the central role of vowels and consonants in language formation and communication.